Quantifying the in-plane strain influence on second harmonic generation of molybdenum disulfide - Huadan Xing; Jibin Liu; Zihao Zhao; Xiaoyong He; Wei Qiu (Communications Physics)
Abstract Quantifying the strain, and even the strain state, is critical for the advancement of strain engineering in microelectronics and optoelectronics fields, whether using the classical semiconductors or emerging two-dimensional materials. Second Harmonic Generation (SHG) has emerged as a potent technique for exploring the optical-mechanical properties of two-dimensional transition metal dichalcogenides (2D-TMDCs). Based on the theoretical framework of SHG, this work analyses the mechanism of different strain states acting on the SHG polarization-intensity spectrum (PIS) of MoS2. A quantifying method is proposed by establishing the analytic relationship between the in-plane strain components and the petal amplitude ratios (PARs) obtained from detected PIS. After calibrating the key parameters of MoS2 SHG PIS, a series of biaxial and uniaxial tensile experiments are performed, whose results are mostly agreed with the theoretical expectations, thus verifying the reliability, correctness and universality of the proposed method for quantitively characterizing the strain state of monolayer MoS2.